Symmetry-breaking in double gyroid block copolymer films by non-affine distortion. (June 2021) - Jo, Seungyun; Park, Haedong; Jun, Taesuk; Kim, Kwangjin; Jung, Hyunsoo; Park, Sungmin; Lee, Byeongdu; Lee, Seungwoo; Ryu, Du Yeol
Highlights: The z -directional contractions of the gyroid films immediately upon deswelling create a unique non-affine distortion. Our X-ray analysis and experimental electron-density difference maps support a notable symmetry-breaking in non-affine gyroid structure. Level-set approach quantitates the structural characteristics of the maps in terms of inversion symmetry-breaking. We envision that a P -breaking gyroid structure may serve as Weyl PhC working at optical frequencies. Abstract: Soft-matter bicontinuous networks find a double gyroid structure from block copolymer (BCP) self-assembly. A gyroid structure composed of dissimilar blocks has proven its potential as a soft crystal capable of tuning structural periodicity and symmetry, of which the lattice dimension is variable with molecular weight of the polymer. Using an asymmetric polystyrene- b -poly(methyl methacrylate) (PS- b -PMMA), here we show that the self-assembled gyroid films formed via a solvent vapor annealing (SVA) process undergo unique structural distortion due to directional deformation immediately upon deswelling. During the SVA process with PS- b -PMMA films, transient cylinders developed from the as-cast morphology transform into a cubic gyroid structure in a swollen state. Rapid and spontaneous deswelling processes ̶ the manners in which the films contract along the z-direction while retaining an enlarged lateral dimension of the cubic form ̶ lead to triclinic gyroid structures with z-directional contraction ratios ( Cz ) of 2.5 and 2.0, respectively. Our X-ray analysis reveals that the deswelling process of the swollen gyroid films produces a notable symmetry-breaking in non-affine gyroid structure that elicits several forbidden reflections such as 110 and 200 reflections. For further characterization of the symmetry-breaking, we delineate the structural features of noncubic gyroid films by computing electron-density difference maps assisted with X-ray measurements. Level-set approach is accordingly developed to quantitate the structural characteristics of the maps in terms of inversion symmetry-breaking, suggesting its possible application to optical Weyl photonic crystals. Graphical abstract: Image, graphical abstract